ENERGY AUDITING ASSESSMENT BY ISO 50001 ENERGY MANAGEMENT STANDARD IN UNIVERSITY BUILDING - Songpob Pasvorarotkool; Sulaksana Mongkon (Universitas Ahmad Dahlan Indonesia, 2020)
This research focuses to study the potential of energy auditing in university building following ISO 50001 Energy Management standard. The sample area is Faculty of Animal Science and Technology Building, Maejo University. The scope of area is a lecture building (building A) and conference building (building B). For energy indicators analysis is divided into three levels namely; organization level, system level, and equipment level. The results found that the sample building used 100% of electricity or about 166,041.66 kWh/year. The significant energy use (SEU) area was the air conditioning system that consumed the highest energy use about 38.33%, following by the lighting system, other systems, lift system, ventilation system and pump system which their proportion are 30.76%, 28.32%, 1.43%, 0.95%, and 0.21, respectively. The energy utilization index (EUI) before the study is equal to 5.49 kWh/m2âˆ™year higher than after the study assessment that is equal to 3.75 kWh/m2âˆ™year from four recommended measures for example; lighting bulb reducing in the brighter area than standard, changing the fluorescent bulb to LED bulb, changing air conditioning to use a high-efficiency air conditioner, and reducing time ventilation fans in the air-conditioned room. If the sample building will improve following recommended measures, the expected result is a great saving than the current situation. The energy performance index (EPI) of will be decreased by about 31.63%. The electricity will be saved of 32,239.38 kWh/year or equivalent to 125,088.78 Baht/year which the investment cost is about 682,075.00 Baht and get a payback period of 5.45 years.